PENGARUH PENERAPAN MODEL COOPERATIVE LEARNING TIPE THINK PAIR SHARE BERBASIS PEER TUTORING TERHADAP PENINGKATAN HASIL BELAJAR IPAS PESERTA DIDIK SDN 12 RAWAJITU UTARA - Aria Dian Indiani; Alif Luthvi Azizah; Agung Dian Putra; Ulwan Syafrudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
One of the main problems in this study is the low learning achievement of fourth-grade students at SD Negeri 12 Rawajitu Utara. Specifically, only 45.45% of fourth-grade students and 31.82% of fourth-grade students met the Learning Objectives Achievement Criteria (KKTP) with a score of 70 or above. The purpose of this study was to determine how well fourth-grade students in an elementary school environment learn when they use the Think Pair Share Cooperative Learning approach, which is based on peer guidance. By using a non-equivalent control group design, this approach is a quasi-experimental approach. In this study, 44 fourth-grade students will be involved; 22 will be the control group, and 22 will be randomly assigned to the experimental group using purposeful selection. The control group uses the STAD Cooperative Learning model, while the experimental group uses a peer-guidance-based model called Think Pair Share Cooperative Learning. A simple linear regression test was used to assess data obtained from 20 previously validated multiple-choice questions covering cognitive areas C2–C5. The findings showed that the experimental group had a higher mean posttest score (76) compared to the control group (71), and the N-Gain value of the experimental group was 0.5, which is in the moderate range, while the value of the control group was 0.4. The R Squared value was 0.412 and the significance value was 0.001, indicating that the model explained 41.2% of the variation in student learning outcomes, according to the regression test.